A DNA tweezers-actuated regenerated DNAzyme nanoreactor: a fluorescence sensor for miRNA and adenosine detection. Issue 12 (11th March 2020) - Chen, Xueying; Fu, Xinrui; Wu, Yuanyu; Jin, Yifan; Li, Wei
Abstract : A DNA tweezers-actuated controllable and regulatable DNAzyme nanoreactor was developed for cancer-related miRNA and adenosine detection. Abstract : A DNA tweezers-actuated regenerated DNAzyme nanoreactor has been constructed. DNA tweezers that can be reversibly switched between the open and closed states were designed and served as a scaffold to regulate the DNAzyme. In the original open state, the split DNAzymes were spatially separated at the two tweezers arms without catalytic efficiency. When fuel strands were added, the tweezers converted to a closed state that holds the two tweezers arms close together, forming an integral DNAzyme with an active secondary structure. Then the active DNAzyme could catalyze the substrate cleavage with the aid of cofactors, generating detectable and amplified signals. Especially, the DNA tweezers could switch back to the original open state when fresh set strands were added, resulting in the separation of the split DNAzymes. The regulation of the DNAzyme nanoreactor was achieved for four cycles, and the DNAzyme nanoreactor could be regenerated for consecutive target detection. Moreover, as a fluorescence biosensor, the proposed DNAzyme nanoreactor has been applied in miRNA and adenosine detection, exhibiting excellent sensitivity, specificity, and perfect capability for practical application. Thus, it provides a reusable platform for clinical detection and could be further applied in clinical early diagnosis and treatment.